Cut slopes in clayey soils: consolidation and overall stability by finite element method - José Leitão Borges (2008)
When a cut slope in a saturated clay is undertaken, a transient water flow occurs and stress transferences from the water to the soil skeleton take place in time (consolidation). Mainly in strongly overconsolidated clays, these stress transferences may determine swelling of soil and therefore reduction of its shear strength in time. However, the lowering of the water level associated to the cut increases effective mean stress, which may therefore counterbalance the above-mentioned effect. In the paper, the behaviour of a cut slope in an overconsolidated clay is analysed by a finite element program that incorporates the Biot consolidation theory (coupled analysis), with constitutive relations simulated by the p-q-θ critical state model. In addition, the variation in time of the overall stability is assessed with a computer program that uses the finite element results and formulations of the critical state soil mechanics. In order to achieve a more complex geotechnical interpretation of the problem, the analysis in time of the excess pore pressures, effective stresses, displacements and stress levels is also presented. Finally, comparisons of stability results are analysed by changing some parameters, namely the problem geometry (weight of excavated soil) and the over-consolidation ratio of the clay